ANALISIS DISIPLIN KERJA PEGAWAI MELALUI FAKTOR PEMBERIAN KOMPENSASI PT. JAPFA COMFEED INDONESI Tbk. CIREBON - Kurniawan, Zuki (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2019)
Basically, humans want to work is to meet the needs of both physical and spiritual needs. If relative needs are met then the serenity and concentration of work will increase so that discipline will be better. Work discipline will improve work effectiveness and productivity.Increased work productivity will further ensure the achievement of goals and continuity of the company. In improving the productivity of work leaders must strive to provide welfare in the form of adequate compensation both in the form of material and non-material to employees in order to increase work discipline. When satisfaction is achieved from work, this will stimulate them to improve their work discipline, so that work productivity increases and the goals and goals of the company will be achieved. In the preparation of this thesis researchers took the object of research on most employees at PT. Japfa Comfeed Indonesia Tbk. Cirebon with permanent employees status. With the reason that the level of compensation obtained by employees is closely related to the level of discipline in an effort to optimize the company's goals. From the results of the above research can authors conclude as follows: 1. Implementation of compensation, PT.Japfa Comfeed Indonesia Tbk. Cirebon can be said to be good, but still need more improvement. 2. Employee discipline level of PT Japfa Comfeed Indonesia Tbk., Still need to be improved again this will impact to decreasing overall performance. 3. From the results of the correlation test of 0.857 states that a strong / strong relationship between the variable compensation with the variable discipline. At the real level = 0.05 from the result of analysis it turns out H: P> 0 received, that is very high correlation, which means between variable compensation (X) with variable discipline (Y) there is a very high/ strong relationship with H alternative accepted, hypothesis 0 rejected, supported with result that t count> t table that is 7,05> 1,725.